2009
DOI: 10.1128/iai.00355-09
|View full text |Cite
|
Sign up to set email alerts
|

Opa+and OpaIsolates ofNeisseria meningitidisandNeisseria gonorrhoeaeInduce Sustained Proliferative Responses in Human CD4+T Cells

Abstract: T cells may interact with a number of bacterial surface antigens, an encounter which has the potential to downmodulate host immune responses. Neisseria meningitidis, a human colonizer and an agent of septicemia and meningitis, expresses Opa proteins which interact with the CEACAM1 receptor expressed on activated T cells. Since CEACAM1 can act as an inhibitory receptor and T cells in subepithelial tissues may encounter whole bacteria, which often express Opa proteins in vivo, this study assessed primarily if Op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 45 publications
0
25
1
Order By: Relevance
“…This inhibitory effect in the form of reduced T cell cytokine production, proliferation or cytotoxic activity, has been observed in vitro when human peripheral-blood-derived mononuclear cells (PBMCs) were stimulated with T cell activators in the presence of CEACAM1-specific antibodies or Opa proteins of N. meningitidis or Neisseria gonorrhoeae [12,13]. By contrast, other experiments including by our own group found no inhibitory effect of the presence of Opa protein on N. meningitidis or N. gonorrhoeae induced CD4+ T cell responses [15]. A few studies using immobilized CEACAM1 on activated T cells even resulted in opposite effects in which T cell proliferation was enhanced [16,24].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…This inhibitory effect in the form of reduced T cell cytokine production, proliferation or cytotoxic activity, has been observed in vitro when human peripheral-blood-derived mononuclear cells (PBMCs) were stimulated with T cell activators in the presence of CEACAM1-specific antibodies or Opa proteins of N. meningitidis or Neisseria gonorrhoeae [12,13]. By contrast, other experiments including by our own group found no inhibitory effect of the presence of Opa protein on N. meningitidis or N. gonorrhoeae induced CD4+ T cell responses [15]. A few studies using immobilized CEACAM1 on activated T cells even resulted in opposite effects in which T cell proliferation was enhanced [16,24].…”
Section: Introductionmentioning
confidence: 80%
“…These processes are mediated mainly by interaction with carcinoembryonic antigen-related cellular adhesion molecules (CEACAMs) found in a wide variety of human tissues [7][8][9][10][11]. Binding of Opa proteins to CEACAMs also plays a part in interactions with the immune system [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, others have found that Opa proteins expressed on the surface of gonococci (4) arrest activation and proliferation of CD4 ϩ T cells via a CEACAM1-mediated mechanism (24). Data from studies using meningococcal OMVs have yielded conflicting results (24,54). More data on the interaction between Opa proteins and CD4 ϩ T cells are therefore required.…”
Section: Vol 79 2011mentioning
confidence: 99%
“…In the female genital tract, squamous epithelia express CEACAM5, whereas CEACAM1 is expressed on columnar epithelia of the endocervix and uterus (27), allowing each to be accessible for direct docking by the gonococci. Moreover, CEACAM1 is widely expressed on lymphocytes, and CEACAM1-induced signaling can influence immune cell activation (28)(29)(30)(31)(32)(33)(34)(35), potentially providing a mechanism for immune evasion by N. gonorrhoeae. While no study to date has looked at CEACAM expression within the male urethra, a transgenic mouse line expressing human CEACAMs in a manner that closely reflects the spatiotemporal expression pattern in humans expresses CEACAM5 on the urethral mucosal surface (36).…”
mentioning
confidence: 99%